Loss of sales due to incorrect forecasting of demand - Ríos Treviño, Andrea; Valdez Contreras, Sergio Alejandro (UANL. Facultad de Contaduría Publica y Administración, 2014)
The main objective is to gather and document the information about the solution process a Mexican company followed. The problem was the loss of sales due to a forecasting error in demand. The company determined a supposition of what they thought was the cause to their problem was forecasting error in demand. There are different methods and techniques that can be used in solving such problem. They performed different stages of a known methodology, known as Total Quality Management. This methodology requires to measure, calculate, evaluate, plan and improve processes or tools in order to achieve, the set goal. In the end, results were very positive, although the use of a more robust forecasting method was necessary to be more successful.